Size‐resolved counting of circulating tumor cells on pinched flow‐based microfluidic cytometry. Issue 1 (8th September 2022) - Xia, Ling; Zhou, Wanjun; Huang, Jianying; Dong, Jianwei; Xiao, Xiaohua; Li, Gongke
Abstract: Precise cell detecting and counting is meaningful in circulating tumor cells (CTCs) analysis. In this work, a simple cyclic olefin copolymer (COC) microflow cytometer device was developed for size‐resolved CTCs counting. The proposed device is constructed by a counting channel and a pinched injection unit having three channels. Through injection flow rate control, microspheres/cells can be focused into the centerline of the counting channel. Polystyrene microspheres of 3, 9, 15, and 20 µm were used for the microspheres focusing characterization. After coupling to laser‐induced fluorescence detection technique, the proposed device was used for polystyrene microspheres counting and sizing. A count accuracy up to 97.6% was obtained for microspheres. Moreover, the proposed microflow cytometer was applied to CTCs detecting and counting. To mimic blood sample containing CTCs and CTCs mixture with different subtypes, an MDA‐MB‐231 (human breast cell line) spiked red blood cells sample and a mixture of MDA‐MB‐231 and MCF‐7 (human breast cell line) sample were prepared, respectively, and then analyzed by the developed pinched flow‐based microfluidic cytometry. The simple fabricated and easy operating COC microflow cytometer exhibits the potential in the point‐of‐care clinical application.